Effectiveness of Accounting Information Systems, Locus of Control and Work Culture on Employee Performance at LPD Kuta - KURNIAWAN, I Kadek; NARINDRA, Anak Agung Ngurah Mayun; PUTRA, I Wayan Gede Yogiswara Darma (PT Batara Swastika Harati, 2023)
This research aims to test and analyze the influence of Accounting Information System Effectiveness, Locus of Control and Work Culture on Employee Performance. This research was conducted at the LPD in Kuta District with a research sample of 98 respondents taken using a purposive random sampling technique. All data obtained from the questionnaire distribution is suitable for use, then analyzed using multiple linear regression, hypothesis testing (t test and f test). The results of the research show that, (1) The effectiveness of the Accounting Information System has a positive and significant effect on Employee Performance at the LPD in Kuta District. This shows that the better or increased the effectiveness of the Accounting Information System, the greater the employee performance at the LPD in Kuta District. (2) Locus of Control has a positive and significant effect on Employee Performance at the LPD in Kuta District. This shows that the better or increased the Locus of Control, the greater the employee performance in motorized vehicles at the LPD in Kuta District. (3) Work Culture has a positive and significant effect on Employee Performance at the LPD in Kuta District. This shows that the better or improved the work culture, the greater the employee performance at the LPD in Kuta District.